PENGARUH KEDISIPLINAN, BUDAYA ORGANISASI DAN KOMPETENSI PEGAWAI TERHADAP TINGKAT KEPUASAN PIMPINAN PADA STASIUN KARANTINA PERTANIAN KELAS I TANJUNGBALAI ASAHAN - Hendra Bangsawan Daulay; Bahrumsyah Putra; Syariah .; Rahma Ayuni; Nafisah . (Jurnal Prodi Fakultas Ekonomi-UISU, 2021)
The formulation of the problem in this study are: How do discipline, organizational culture and competence influence the level of leadership satisfaction. This study aims to examine how discipline, organizational culture and competence influence the level of leadership satisfaction. With total sampling technique, the sample in this study amounted to 51 people. Discipline variable partially has a positive effect on the level of leadership satisfaction; Organizational culture variables partially have a positive effect on the level of leadership satisfaction; Employee competency variables partially have a positive effect on the level of leadership satisfaction; Discipline variables, organizational culture and employee competence simultaneously have a positive and significant effect on the level of leadership satisfaction